Pancasila dan demokrasi: Keterlibatan masyarakat dalam proses politik di era millenial - putri, aulia mecca (Maliki Interdisciplinary Journal, 2025)
Pancasila, as the foundation of the Indonesian state, serves as the primary foundation for the implementation of a just and nationally distinctive democracy. In the millennial era, public involvement in the political process has grown in line with the rapid development of information technology and social media. This article examines the relationship between Pancasila and democracy, and how the millennial generation plays a role in maintaining the quality of democracy through active participation. The analysis shows that Pancasila provides moral direction for Indonesian democracy, while millennials play a strategic role in building a healthy democracy through political literacy, digital participation, and strengthening the value of deliberation. Thus, it can be concluded that strengthening Pancasila values ​​in democratic practices is key to realizing a harmonious and just national life. The millennial generation is expected to be not only users of technology but also agents of change, capable of channeling aspirations wisely, critically, and responsibly in accordance with the spirit of Pancasila. Through the collaboration between the noble values ​​of Pancasila and the active participation of the younger generation, Indonesian democracy can continue to develop healthily, ethically, and firmly rooted in the nation’s identity.